Complex Relationship of Body Mass Index with Mortality in Patients with Critical Limb Ischemia Undergoing Endovascular Treatment. Issue 3 (March 2015) - Murata, N.; Soga, Y.; Iida, O.; Yamauchi, Y.; Hirano, K.; Kawasaki, D.; Fujihara, M.; Tomoi, Y.
Abstract : Objective: To investigate the relationship between body mass index (BMI) and long-term outcomes of patients with CLI after endovascular treatment (EVT). Design: Retrospective multicenter study. Subjects: 1088 consecutive patients (1306 limbs, mean age 72 ± 10 years) with CLI who underwent EVT for isolated infrapopliteal artery lesions were evaluated. These subjects were identified in the J-BEAT III registry. Methods: The patients were divided into groups based on BMI <18.5 kg/m 2 (underweight, n = 188; 219 limbs), 18.5 to 24.9 kg/m 2 (normal weight, n = 718; 868 limbs), and >25.0 kg/m 2 (overweight/obese, n = 182; 219 limbs). The endpoints were overall survival and freedom from major adverse limb events (MALE). Results: The median follow up period was 1.5 years (range: 1 month–8.7 years). The 3 year overall survival rates were 33.3%, 61.2%, and 69.8% in underweight, normal, and overweight/obese patients, respectively. The survival rate was significantly lower in underweight patients and significantly higher in overweight/obese patients compared with patients of normal weight (both p < .0001). The 3 year rates of freedom from MALE did not differ significantly among the three groups (36.4%, 45.4%, and 52.3%, respectively, p = .32). Age, BMI <18.5 kg/m 2, heart failure, aortic valve stenosis, renal failure, triglyceride levels, serum albumin <3.0 g/dL, anticoagulant treatment, non-ambulatory status, and Rutherford 6 classification all were significantly associated with overall survival. Conclusions: BMI has a complex correlation with mortality in patients with CLI after EVT for isolated infrapopliteal artery lesions. Underweight patients with CLI have an extremely poor prognosis. Such patients have many other factors associated with mortality, but low BMI was identified as an independent predictor of a poor prognosis in patients with CLI. Similarly, normal weight patients had a small but significant increase in mortality compared with overweight/obese patients.